(untitled) (Global Journal of Medical Research, 2015)
Tuberculosis (TB) is disproportionately affects the most economically disadvantaged strata of society. Many studies have assessed the association between poverty and TB, but only a few have assessed the direct financial burden TB treatment and care can place on households. Patient costs can be catastrophic health expenditure for TB affected households in Particularly Vulnerable Tribal Groups (PVTGs). A survey of pulmonary tuberculosis (PTB) was carried out in Saharia dominated Pohri Block of Shivpuri district of Madhya Pradesh state in central India during the period 2013 to 2014. Of 9964 surveyed, 280 PTB cases identified formed the study population for the present study. Among 280 TB patients identified, 220 (79%) cases interviewed at their residence by trained field investigators after obtaining written informed consent. This study demonstrates the economic burden in terms of direct, indirect and total costs for both diagnosis and treatment. In our sample, majority getting treatment free of costs and those who incurred costs, they faced catastrophic TB care expenditure amounted to 10%, which is the proportion of various costs in relation to annual family income. TB is a major cause of impoverishment, as it puts a heavy burden on the family budget, which can force families to absolute poverty.